Effect of Silica Fume on Some Properties of No-Fine Concrete with Recycled Coarse Aggregate (Journal of Engineering, 2024)
No-fines Concrete is a lightweight porous concrete produced by omitting sand from the traditional concrete mix. It helps replenish the groundwater aquifer by directly allowing precipitation to seep into the earth thanks to its wide pores. This work studied the influence of partially replacing cement with silica fume (SF) with percentages of 5, 8, and 10% on some properties of no-fine concrete made using recycled coarse aggregate. The natural coarse aggregate (NA) was replaced with 10%, 20%, and 30% by crushed reactive powder concrete waste volume as recycled aggregate (RA). The optimum percentage was 10% RA with 10% SF, which indicated a substantial improvement in the no-fine concrete's strength, dry density, and water absorption compared to the design mix. The results exhibit increases in percentages in compressive strength, tensile strength, flexural strength, and dry density by 18%, 14%, 16%, and 1%, respectively, while exhibiting a decrease in water absorption by 5% at 28 days.